GROWTH RATE AND MORTALITY POPULATION OF Ompok hypophthalmus IN THE LUBUK SIAM LAKE, LUBUK SIAM VILLAGE, KAMPAR REGENCY , RIAU PROVINCE - Alfayeat, Rindo; M. Fauzi, M. Fauzi; Adriman, Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract Ompok hypophthalmus is one of valuable commodity, and it is a  native species in the Riau.  High intensity of uncontrolled fishing causes the extinction of that species. A research aims to understand the growth rate, mortality, and exploitation rate of the fish in the Lubuk Siam Lake has been conducted in May-July 2019. The fish was sampled using gill nets. Data were analyzed using FiSAT II program. Results shown that the Von Bertalanffygrowth parameters L∞.= 249.9 mm ; K= 0.57 /year, and t0 = -0.2995/ year.Total mortality(Z) = 2.19 ,natural mortality (M) = 1.32,  mortality of catch (F) = 0.87 and level of exploitation (E) = 0.40  and it is slightly below the maximum capture value. Length and weight relationship of the fish in the Lubuk Siam Lake was 2.711 (negative allometric). Keywords: Von Bertalanffy, native fish, oxbow lake, Length-weight relationship